Weed Management in Home Lawns - Joseph Bryan Unruh; Barry Brecke; Laurie E. Trenholm (EDIS)
Weeds can simply be defined as unwanted plants or plants growing out of place. The proper identification of weeds and some understanding of how and why weeds are present in a lawn are important in selecting the best control strategy. Knowledge of whether or not weeds were previously present in a particular area will also help the homeowner prepare for control procedures in the future. Weed control should be a carefully planned and coordinated program instead of a hit-or-miss operation. This document is ENH884, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 3, 2003.